The trophic ecology of waterbirds in a small temperate estuary: a stable isotope and lipid tracer approach - Hean, Jeffrey William (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
Waterbirds are often overlooked as predators in aquatic ecosystems, despite the fact that waterbirds congregate in great numbers in and around waterways, notably estuaries. To fully appreciate the effect that aquatic feeding waterbird species may have on aquatic prey communities and the role that they play in estuarine food webs, stable isotopes and fatty acid profiles were employed to examine the seasonal diet of selected waterbirds in the Kowie Estuary, Eastern Cape Province, South Africa. Population counts were conducted every month for four seasons to examine the demography of waterbirds in the lower reaches of the estuary. The mean monthly energy consumption, along with dry matter intake of all waterbird species observed, were calculated and compared to similar estuaries in South Africa and elsewhere. Three duck species, one migrant sandpiper and one piscivore were selected for more detailed investigation at several temporal scales. This thesis has revealed that stable isotope analysis of waterbird tissues provides more informative data than fatty acid analysis for investigating waterbird diet and basal resource-tertiary consumer nutrient coupling. Stable Î´15N and Î´13C isotopes from several body tissues, in conjunction with SIAR models, were used to determine the seasonal diet of each waterbird species, while fatty acid profiles were investigated to examine the trophic transfer of fatty acids from basal resources to waterbird predators via the benthic fauna. Stable isotopes revealed that Cape Shoveller, Cape Teal and Yellow-Billed Duck shifted their diet over both long and short temporal scales, while the migratory Ruff and piscivorous Little Egret maintained a relatively consistent diet over time. Isopods, amphipods, copepods and Mysidacea were the main foods of all three duck species and the Ruff (>30%). Little Egret fed mainly on flathead mullet throughout the year. Fatty acid analysis revealed evidence for trophic transfer of specific fatty acids from basal resources to waterbirds in the Kowie Estuary but provided little information on seasonal diet of waterbirds. Waterbirds foraging in the Kowie Estuary appeared to shift their diet to coincide with resource abundance pulses, but also displayed seasonal dietary overlap. This study highlights the role that waterbirds play in aquatic food webs. The subject requires more attention so that we can better understand all the predatory drivers on aquatic communities.
Keywords: Uncatalogued